Partial weight bearing of the tibia. Issue 8 (August 2016) - Ganse, Bergita; Yang, Peng-Fei; Gardlo, Jenny; Gauger, Peter; Kriechbaumer, Andreas; Pape, Hans-Christoph; Koy, Timmo; Müller, Lars-Peter; Rittweger, Jörn
Abstract: Introduction: Partial weight bearing is part of treatment schemes in orthopedic surgery and traumatology. The aim of the present study was to explore to what degree ground reaction forces during partial weight bearing of the lower leg are related to given instructions and to tibia deformation. Materials and methods: Tibia deformation (torsion, medio-lateral and anterio-posterior bending) was measured for rear foot and forefoot loading, 10 kg, 20 kg and half body weight instructions compared to full loading in five healthy male subjects using the "Optical Segment Tracking" approach, a motion-capturing based method that uses monocortically fixed bone screws. Results: 1. Ground reaction force was a good indicator of tibia deformation. 2. Participants significantly under-loaded during half-body weight instructions ( P  < 0.001) while they overloaded when loading the forefoot only. 3. Partial-loading instructions led to a highly significant and systematic reduction in peak ground reaction force (GRFpk) in all three types of tibia deformation with substantial variation between measurements. 4. Forefoot usage was associated with significant, albeit moderate increases in GRFpk ( P  = 0.0031), in AP-bending ( P  = 0.0027) and in torsion ( P  < 0.001), compared to rear foot loading. Discussion: These findings result in the following clinical "lessons learned": 1. GRF is a good reflection of loading-induced deformation of the tibia. 2. GRFs are hard to control by subjects/patients. 3. The expectation that forefoot-loading results in larger tibia deformation could not be confirmed in our study. 4. When aiming at a reduction in tibia deformation, rear-foot loading is more preferable than forefoot loading.